Answer:
(4,3) (2,−3)
Step-by-step explanation:
x^2 =2(−9+3x)+10
2(−9+3x)+10
x2 = −18+6x+10
x2=6x−8
x2−6x+8=0
We now have to find integers that find product is 8 and whose sum is −6
= -4 -2 we find this is set to 4 2 as x−4=0
Add 4 to both sides of the equation. x=4
Set the next factor equal to 0
x−2=0 Add 2 to both sides of the equation.x=2
Confirms and proves x = 4, x = 2
We solve for y
2y+10=(4)2
2y+10=16
2y=16−10
2y = 6
y = 3
We rewrite and solve for y again
(2)^2=2y+10
2y+10=(2)*2
2y+10=4
2y = 4(-10)
2y = -6
y= -3